Optimization of neuron-specific interfering peptides targeting GABAB receptor downregulation for proteolytic stability for conferring neuroprotection in a mouse model of cerebral ischemia - Hleihil, Mohammad; Bhat, Musadiq A.; Grampp, Thomas; Benke, Dietmar (Frontiers in Pharmacology, 2025)
BackgroundCerebral ischemia triggers a cascade of detrimental events, leading to brain damage mainly due to the over-excitation of neurons. Currently, clinically applicable neuroprotective treatments to stop progressive neuronal death remain elusive. The GABAB receptor, crucial for neuronal inhibition, is a promising target for neuroprotection because it inhibits neuronal over-excitation which otherwise leads to excitotoxic death. However, ischemic conditions impair GABAB receptor function by downregulating the receptors via pathologically altered trafficking events. Previously, we developed interfering peptides to inhibit the interaction of GABAB receptors with key interacting proteins, leading to the pathological downregulation of the receptors. These interfering peptides restored GABAB receptor expression and function, resulting in reduced excitability and death of neurons in in-vitro and ex-vivo models of cerebral ischemia. However, the interfering peptides were not effective in-vivo because of their limited proteolytic stability after systemic application.Methods/resultsHere, we aimed to render three interfering peptides resistant to proteolytic degradation by replacing natural L-amino acids by D-amino acids. Additionally, we optimized a blood brain barrier shuttle (BBBpS) sequence derived from the Rabies virus glycoprotein (RVG) that mediates neuron-specific uptake and blood-brain barrier crossing of these interfering peptides. By optimizing the peptides, we developed stable, neuron-specific interfering peptides that successfully restored GABAB receptors expression and prevented neuronal death following excitotoxic stress in cultured neurons. In vivo testing in the middle cerebral artery occlusion (MCAO) mouse model of cerebral ischemia demonstrated the neuroprotective activity of the optimized peptides by a significantly reduced infarct size.ConclusionThese findings confirm the potential of these peptides as neuroprotective agents and emphasize the importance of proteolytic stability of peptide drugs for their successful in-vivo application.